Study of an innovative combined absorption-adsorption cooling system employing the same evaporator and condenser - M. Hassan; Ibrahim I. El-Sharkawy; K. Harby (Case Studies in Thermal Engineering, 2023)
In this paper, the performance of innovative combined absorption and adsorption cooling (ABC-ADC) systems employing the same evaporating and condensing units is theoretically investigated. The generator of the absorption cooling (ABC) system is connected directly to the heat source system, and the outlet hot water is used to drive the desorber bed of the adsorption cooling (ADC) system. The performance of the proposed system is compared with a separated ABC-ADC system, combined ABD-ADC employing the parallel operation mode, conventional single-stage ADC cycle, and other integrated systems available in the literature. In the separated system, each system of ABC and ADC has its condenser and evaporator. Results showed that, at 85 °C heat source temperature, the cooling capacity and COP of the proposed combined ABD-ADC configuration are 0.344 kW and 0.623, respectively, and higher than that of the separated ABC, and ADC systems by 4.06% and 2.73%, respectively. The cooling capacity and COP of the proposed combined ABD-ADC configuration are significantly higher than that of the single-stage ADC system by 58.34% and 27.07%, respectively. The outlet chilled water temperature fluctuation of the proposed combined ABC-ADC systems (±0.88 °C) is significantly lower than that of the separated ABC-ADC system (±1.84 °C). Validation of the proposed ABC and ADS mathematical models with other published experimental data are around 0.2% and ±10% respectively.